2000
DOI: 10.1136/bmj.321.7275.1501
|View full text |Cite
|
Sign up to set email alerts
|

Relation between private health insurance and high rates of caesarean section in Chile: qualitative and quantitative study

Abstract: Objectives To explore the circumstances and factors that explain the association between private health insurance cover and a high rate of caesarean sections in Chile. Design Qualitative analysis of audiotaped in-depth interviews with obstetricians and pregnant women; quantitative analysis of data from face to face semistructured interview survey conducted postnatally (with women who had given birth in the previous 24-72 hours), and of a review of medical notes at a public hospital, a university hospital, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
153
2
15

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(178 citation statements)
references
References 9 publications
5
153
2
15
Order By: Relevance
“…Results from one national US survey of mothers found little interest in a future elective primary cesarean with just 6% of primiparous mothers interested in that option in the future. 9 Research from other countries with high cesarean rates, most notably Brazil 10 and Chile, 11 have found that, rather than the cesarean rate being driven by maternal demands, it is the interaction between mothers and their providers that leads to the decision to perform a cesarean without a clear medical indication. For example, in Potter's study in Brazil, 10 more than 80% of primiparous mothers in the study anticipated a vaginal birth 1 month before their due date, yet almost half of these mothers (66% in private hospitals) ended up with a cesarean.…”
Section: Mothers' Perspectivesmentioning
confidence: 99%
“…Results from one national US survey of mothers found little interest in a future elective primary cesarean with just 6% of primiparous mothers interested in that option in the future. 9 Research from other countries with high cesarean rates, most notably Brazil 10 and Chile, 11 have found that, rather than the cesarean rate being driven by maternal demands, it is the interaction between mothers and their providers that leads to the decision to perform a cesarean without a clear medical indication. For example, in Potter's study in Brazil, 10 more than 80% of primiparous mothers in the study anticipated a vaginal birth 1 month before their due date, yet almost half of these mothers (66% in private hospitals) ended up with a cesarean.…”
Section: Mothers' Perspectivesmentioning
confidence: 99%
“…La incidencia tanto de placenta previa y acretapercreta está aumentando. Esto principalmente por el aumento de los partos por operación cesárea, lo que es preocupante en nuestro medio, ya que nuestro país exhibe uno de los más altos índices de cesárea del mundo (8).…”
Section: Discussionunclassified
“…Esta patología constituye un desafío a la obstetricia actual dada su frecuente asociación con cicatrices uterinas previas (7) y el importante incremento del parto por cesárea en los últimos años, especialmente en nuestro medio (8), esperándose por consiguiente un aumento en la frecuencia de presentación.…”
unclassified
“…Si bien existen diferencias geográficas en Latinoamérica, la situación de Chile es una de las más preocupantes, con una tasa global de cesáreas cercana al 40% (1). Esta tasa se ha reportado como una de las mas altas del mundo, y se distribuye del 39% al 83% en la práctica privada y del 20% al 28% en los hospitales públi-cos durante el año 2000 (2).…”
Section: Introductionunclassified